2023
DOI: 10.35848/1347-4065/acb2d4
|View full text |Cite
|
Sign up to set email alerts
|

Aerial intense ultrasonic source integrating the horn and vibrating plate

Abstract: The components of conventional high-intensity aerial ultrasonic sources, including the horn, longitudinal vibrating resonance bar, and transverse vibrating plates, are usually constructed separately. In this paper, a compact ultrasonic source that integrates all component parts was developed. First, the structure of the ultrasonic source was designed by simulation analysis with the finite element method. Next, an actual ultrasonic wave source was manufactured, and its electrical characteristics, vibration char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As for the use in wide range of environmental condition, many studies have been reported on micro piezoelectric actuators including ultrasonic transducers. [21][22][23][24] Piezoelectric actuators have the advantages of easy miniaturization and large volumetric output ratio. [25][26][27][28] The disadvantage is that the piezoelectric performance degrades as the temperature decreases, causing a reduction in vibration performance.…”
Section: Introductionmentioning
confidence: 99%
“…As for the use in wide range of environmental condition, many studies have been reported on micro piezoelectric actuators including ultrasonic transducers. [21][22][23][24] Piezoelectric actuators have the advantages of easy miniaturization and large volumetric output ratio. [25][26][27][28] The disadvantage is that the piezoelectric performance degrades as the temperature decreases, causing a reduction in vibration performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many high-power devices using piezoelectric ceramics have been manufactured for practical use and developed to be highly beneficial for enabling advancements in the fields of robotics and medical technology. [1][2][3][4][5][6] These devices driven by electromagnetic devices are difficult to miniaturize for their complicated structure and decrease output power strictly with gears. Piezoelectric devices have a high output power density maintained through miniaturizing.…”
Section: Introductionmentioning
confidence: 99%